THE PURPOSE AND OBJECTIVE OF THE STUDY, ITS LOGIC (Journal of Universal Science Research, 2023)
The article discusses the features of research in the field of logic. The work gives characteristics of logical and non-logical terms, examines the features of empirical and theoretical logical terms, and provides logical and methodological criteria for the scientific and non-scientific nature of knowledge.